AB0103 Humoral Immunity To Food Antigens in Patients with Early Steroid and BMARD Naïve Rheumatoid Arthritis. (15th July 2016) - Grujic, M.; Zlatanovic, M.; Prodanovic, S.; Matic, I.; Djordjic Crnogorac, M.; Damjanovic Velickovic, A.; Kolundzija, B.; Besu, I.; Juranic, Z.; Babic, D.; Damjanov, N.
Abstract : Background: The presence of different antibodies in the serum of patients with rheumatoid arthritis (RA) before detectable joint inflammation points to a source of RA autoimmunity different then synovium. Recent data [1] support that RA-related autoimmunity may originate at a mucosal site: oral, lung and gastrointestinal mucosa. Special emphasis is on the antibodies of IgG class and their effector function of binding to Fc gamma receptors (FcRγ) on many different immune cells. Objectives: The aim of this study was to investigate the presence and possible association between humoral immunity to food antigens and disease activity in patients with early treatment naive RA (eRA). Also, we examined the expression of FcRγ (CD16) on lymphocytes, NK cells and granulocytes in peripheral blood of these patients and its possible relation with humoral food immunity. Methods: Study included 50 patients newly diagnosed with RA, who had not received any corticosteroid or DMARD therapy and whose conventional radiographs of hands and feet showed no structural damage. Control group consisted of 106 healthy volunteers. The presence and intensity of serum IgG, IgA and IgM antibodies to cow's milk proteins (CMP) and gliadin were determined by ELISA assays. The expression of CD16 and CD56 on immunocompetent cells of peripheral blood was performed by flow cytometry. Results: Significantly enhanced levels of IgG antibodies to gliadin were detected in patients with eRA in comparison with healthy controls (p=0.028). Levels of IgA and IgM antibodies to CMP were significantly higher in sera of eRA patients compared to healthy controls (p=0.0009, p<0.0001, respectively). The percentage of CD16+ lymphocytes and CD16+CD56+ cells in peripheral blood were significantly decreased in patients with eRA compared to healthy controls (p<0.0001, p<0.0001, respectively). No significant difference in the percentage of CD16+ granulocytes in peripheral blood between the examined groups was detected, however significantly higher mean fluorescence intensity (MFI) of CD16 on granulocytes was detected in patients with eRA (p<0.0001). MFI of CD16 expression on lymphocytes was significantly increased in patients with eRA in comparison with healthy individuals (p=0.004). The significant decrease in the percentage of lymphocytes in patients with eRA (p=0.002) was detected. Positive correlation was found between IgG anti-gliadin antibodies and CD16 expression on lymphocytes (r=0.360, p=0.025). Furthermore, these antibodies inversely correlated with the percentage of CD16+ granulocytes (r=-0.326, p=0.045). Conclusions: Significantly higher levels of antibodies to food antigens like gliadin and CMP are present in sera of patients with eRA and could have possible role in the early stages of this disease through activating IgG receptors on immunocompetent cells. References: Demoruelle MK, Deane KD, Holers VM. When and where does inflammation begin in rheumatoid arthritis? Curr Opin Rheumatol 2014; 26:64–71. Disclosure of Interest: None declared